Anomalous hexagonal superstructure of aluminum oxide layer grown on NiAl(110) surface. (11th October 2016) - Krukowski, Pawel; Chaunchaiyakul, Songpol; Minagawa, Yuto; Yajima, Nami; Akai-Kasaya, Megumi; Saito, Akira; Kuwahara, Yuji
Abstract: A modified method for the fabrication of a highly crystallized layer of aluminum oxide on a NiAl(110) surface is reported. The fabrication method involves the multistep selective oxidation of aluminum atoms on a NiAl(110) surface resulting from successive oxygen deposition and annealing. The surface morphology and local electronic structure of the novel aluminum oxide layer were investigated by high-resolution imaging using scanning tunneling microscopy (STM) and current imaging tunneling spectroscopy. In contrast to the standard fabrication method of aluminum oxide on a NiAl(110) surface, the proposed method produces an atomically flat surface exhibiting a hexagonal superstructure. The superstructure exhibits a slightly distorted hexagonal array of close-packed bright protrusions with a periodicity of 4.5 ± 0.2 nm. Atomically resolved STM imaging of the aluminum oxide layer reveals a hexagonal arrangement of dark contrast spots with a periodicity of 0.27 ± 0.02 nm. On the basis of the atomic structure of the fabricated layer, the formation of α -Al2 O3 (0001) on the NiAl(110) surface is suggested.